Pathogenic gene variation spectrum and carrier screening for Wilson's disease in Qingdao area. Issue 8 (9th July 2021) - Qiao, Lingyan; Ge, Juan; Li, Cheng; Liu, Yusheng; Hu, Conghui; Hu, Sicui; Li, Wenjie; Li, Tang
Abstract: Background: Despite the increasing number of reports on the analysis of ATP7B variants, reports on carrier screening for Wilson's disease (WD, OMIM:277900) are rare. Methods: Peripheral blood samples were collected from 42 patients from Qingdao Women and Children's Hospital diagnosed with WD for direct sequencing of ATP7B gene. Twelve hotspot variants of ATP7B were selected for carrier screening in Qingdao area based on an analysis of information related to ATP7B variants and literature reports in China. We screened 5012 dried blood spots (DBSs) from asymptomatic newborns in Qingdao area to estimate carrier frequency. DNA was extracted from dried blood spots. Gene sequencing was performed using multiplex polymerase chain reaction (PCR) combined with second‐generation sequencing. The carrier frequency of each hotspot variant was calculated using the count data (expressed as number of carriers (%) obtained by direct counting. Results: The carrier frequency of 12 hotspot variants was 1.46% (95% CI: 1.16–1.83%). The ATP7B variant with the highest carrier frequency was c.2333G>T, accounting for 54.79% of all variants screened, followed by c.2975C>T and c.2621C>T, accounting for 17.81% and 15.07% of all variants screened, respectively. Conclusion: Carrier frequency of ATP7B gene pathogenic variants is high in the population in Qingdao area. Abstract : This study aimed to understand the carrier frequency of pathogenic variants of ATP7B in WD in the healthy population in Qingdao area, to elucidate the causes for the high incidence of WD in this region and to provide preliminary experience for the implementation of carrier screening for WD.